Allameh Tabatabaei’s view on Monotheistic Ethics - Mustafa Khalili (اخلاق وحیانی, 2011)
By the characteristic of being revealed and monotheistic, monotheistic ethics makes the Islamic Ethics distinguished from other ethical schools.  In today’s societies there are three or even four ethical schools with very long history: Greek Ethical School, Comprehensive Ethical School, Relativism and Elite Ethical School. Although these ethical schools attempt to adjust individual and social manner of their followers, and donate well-trained people to the society in terms of ethical principles, they have different effects on the basis of their specific attitude to human role, human place and purpose of his creation. On the viewpoint of Allameh Tabatabaei becoming ethical, one should become familiar with the teachings of monotheistic, and whole the ethics will be the inception to this human sublime point. In this paper we will examine quiddity and components of monotheistic ethics from the viewpoint of His Highness.